2012
DOI: 10.1073/pnas.1205231109
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Vago restricts West Nile virus infection in Culex mosquito cells by activating the Jak-STAT pathway

Abstract: Although West Nile virus (WNV) and other arthropod-borne viruses are a major public health problem, the mechanisms of antiviral immunity in mosquitoes are poorly understood. Dicer-2, responsible for the RNAi-mediated response through the C-terminal RNase-III domain, also contains an N-terminal DExD/H-box helicase domain similar to mammalian RIG-I/MDA5 which, in Drosophila, was found to be required for activation of an antiviral gene, Vago. Here we show that the Culex orthologue of Vago (CxVago) is up-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
316
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(324 citation statements)
references
References 36 publications
6
316
0
2
Order By: Relevance
“…As insects appear to lack an adaptive immune response characteristic of vertebrates, this controlling response occurs through activation of apparently simple, linear innate immunity pathways. However, in PNAS, Paradkar et al (3) describe a mechanism connecting two of these innate immunity pathways (the RNAi pathway and the Jak-STAT pathway) in mosquitoes through the action of a secreted signaling molecule, Vago, leading to an antiviral state in uninfected, responsive cells. This work provides evidence of an integrated, versatile insect immune system capable of communication between pathways and cells to give rise to an effective response.…”
mentioning
confidence: 99%
“…As insects appear to lack an adaptive immune response characteristic of vertebrates, this controlling response occurs through activation of apparently simple, linear innate immunity pathways. However, in PNAS, Paradkar et al (3) describe a mechanism connecting two of these innate immunity pathways (the RNAi pathway and the Jak-STAT pathway) in mosquitoes through the action of a secreted signaling molecule, Vago, leading to an antiviral state in uninfected, responsive cells. This work provides evidence of an integrated, versatile insect immune system capable of communication between pathways and cells to give rise to an effective response.…”
mentioning
confidence: 99%
“…In fact, evidence suggests that there are significant differences between the different arbovirus families which need to be taken into consideration. Some (or possibly all) flaviviruses have the ability to suppress RNAi [59,101]; thus it is not surprising that other innate immunity pathways such as JAK/STAT and Toll are involved in controlling flavivirus infection in mosquitoes [92,115,130]. In contrast, alphaviruses are not known to actively suppress RNAi and use only decoy mechanisms to evade the RNAi response [111].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that Dcr-2 is also involved in signalling. Like RIG-I or Mda-5 in mammalian cells, Dcr-2 detects dsRNA as foreign and activates signalling which, at least in mosquitoes, results in increased expression of vago, a cytokine with an interferon-like function [92].…”
Section: Mirnasmentioning
confidence: 99%
See 2 more Smart Citations